Mekanisme Eksekusi Putusan Hak Uji Materiil oleh Mahkamah Agung: Analisis Proses dan Implikasinya terhadap Peraturan Perundang-undangan - Tb. Mochamad Ali, Asgar (Primagraha Law Review, 2025)
The mechanism for reviewing regulations under the Act against the Act by the Supreme Court is generally known as material judicial review. This study aims to analyze the mechanism of executing material judicial review decisions by the Supreme Court and its implications for the regulations being reviewed. This study uses a normative legal research approach with statutory and conceptual approaches analyzed through qualitative analysis techniques. This study concludes that: firstly, in the mechanism of executing material judicial review decisions, the Supreme Court plays a crucial role in determining the validity of a regulation, where if it is declared invalid or unenforceable, the relevant agency is required to immediately revoke it. However, Supreme Court Regulation No. 1 of 2011 does not specify a clear timeframe for examining applications, potentially leading to uncertainty and losses for the parties involved. And secondly, material judicial review decisions by the Supreme Court have a unique characteristic, namely being ex tunc or pro futuro, where if the implications of the decision are that the regulation is invalid or annulled, the regulation is considered never to have existed and has no binding legal force. The Supreme Court orders the relevant agency to revoke the annulled regulation within 90 days as a logical consequence of the material judicial review decision.